2023
DOI: 10.3390/microorganisms11061448
|View full text |Cite
|
Sign up to set email alerts
|

A Microbiological Approach to Alleviate Soil Replant Syndrome in Peaches

Abstract: Replant syndrome (RS) is a global problem characterized by reduced growth, production life, and yields of tree fruit/nut orchards. RS etiology is unclear, but repeated monoculture plantings are thought to develop a pathogenic soil microbiome. This study aimed to evaluate a biological approach that could reduce RS in peach (Prunus persica) orchards by developing a healthy soil bacteriome. Soil disinfection via autoclave followed by cover cropping and cover crop incorporation was found to distinctly alter the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Soil sterilization via autoclave may bring strong benefits to plants, particularly in the short term (i.e., within one planting cycle). In a recent study conducted by Newberger et al [29], it was found that plant biomass increased in the first cycle of planting, but in the second cycle, biomass decreased in the soils that were initially autoclaved. Thus, soil sterilization may benefit plant growth and soil microbiome resiliency, especially in the time period of a single planting cycle.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Soil sterilization via autoclave may bring strong benefits to plants, particularly in the short term (i.e., within one planting cycle). In a recent study conducted by Newberger et al [29], it was found that plant biomass increased in the first cycle of planting, but in the second cycle, biomass decreased in the soils that were initially autoclaved. Thus, soil sterilization may benefit plant growth and soil microbiome resiliency, especially in the time period of a single planting cycle.…”
Section: Discussionmentioning
confidence: 94%
“…The soil was then autoclaved using a STERIS autoclave (STERIS, Dublin, Ireland) for three 15 min liquid cycles at 121 • C. Soil was again dried before administering soil into pots. Autoclave sterilization is commonly used in research to reduce soil microbial diversity [27][28][29]. While certain microbial populations attenuate, some taxa can survive and recover rapidly [30].…”
Section: Soil and Plant Selectionmentioning
confidence: 99%